PENAFSIRAN KONSTITUSI DALAM PENGUJIAN KONSTITUSIONALITAS UNDANG- UNDANG TERHADAP UNDANG- UNDANG DASAR 1945 - Tanto Lailam (Jurnal Media Hukum, 2014)
This study is about interpretation of constitution, this study is based on the extent authority of the Constitutional Court on the  interpretation of  the constitution,  including various verdicts that are considered as controversial.The result of the study shows that Constitution 1945 giving authority of the constitution  interpretation of the Constitutional Court to evaluate the conflict of  legal norm, this could be meant that the Constitutional Court is “the guardian of  the constitution and the sole interpreting of constitution” and as the legitimate interpreter of  the constitution.  Some  interesting  in implementing  the  interpretation of  the constitution as a  standard  toevaluate  the conflict of  legal norm, consists of: First, essentially,  that the  interpretation of  the constitution  is one of the ways to elaborate understandings contained in constitution text. Second, related to the independence and the  freedom of judge in using an interpretation method which  is not  regulated by positive  law, therefore the judge is  free to use those interpretation methods which are appropriate with the conviction of the Justice. Justice  in  using  the  interpretation method  doesn’t  only  have  function  as  funnel of  the  act,  but  also  has functioned as the funnel of justice since a judge is required the value of the law and the sense of justice which exists in the society (substantial justice). Refer to  the theory of living constitution, therefore Constitution 1945 should be  understood  as  a  constitution which has  textual  and  contextual  dimention  Third,  the  restriction  in using the interpretation method, the constitutional judge couldn’t only focused into the originalism interpretation method which  only  based  to  original  intent  /  the  formulation  of  Constitution  1945  or  using  the  other interpretations  (non  originalist) which oppositely  those  interpretation  the 1945  Constitution doesn’t work according to system and/ or contended with  the main idea underlying the constitution itself entirely  related to the  purpo  se  that would  like  to be  realized.  Fourth,  the  use of  interpretation method  should  be  able  to  be accounted to  the publics, therefore the validity could be examined  in certain cases. This is very essential to dosince Constitutional Court has an extent interpretation authority so that it could keep justice of Constitutional Court  to avoid it from misuse of authority  in interpreting of 1945 Constitution.